GAME EDUKASI MONOPOLI ANEMIA (GEMA) SEBAGAI MEDIA INOVASI HEALTH EDUCATION YANG DAPAT MEMPENGARUHI PENGETAHUAN REMAJA TENTANG ANEMIA - Neny San Agustina Siregar; Mardiah, Mardiah; Dewi Mey Lestanti Mukodri; Rita Ridayani; Wahyu Eni Setyohari (Pusat Riset dan Inovasi Nasional, 2022)
This study was conducted to determine the effect of the Monopoly Anemia Educational Game (GEMA) as one of the media innovation for Health Education on the behaviour of adolescent girls about anemia in the work area of Tanjungpinang City Health Center in 2021. This type of study is a quasi-experiment with a nonrandomized pretest and posttest with a control group design which is used to determine the effect of the Monopoly Anemia Educational Game (GEMA) as one of the media innovation for Health Education on the behaviour of adolescent girls about anemia in the Tanjungpinang City Health Center in 2021. The sampling technique in this study used the purposive sampling method formula where to obtain data the researchers met the research subjects, namely all adolescent girls in the work area of ​​the Tanjungpinang City Health Center who met the criteria, namely: adolescents who were willing to be sampled, adolescent aged 10-16 years, the adolescent who registered as a youth Integrated Healthcare Center participant in the work area of the Tanjungpinang City Health Center in 2021. The number of samples is calculated using the sample size formula according to the measurement scale of the two unpaired numerical variables for the average estimate of 2 populations, from the formula the total number is 64 people, plus 10% or 2 people to anticipate if there are respondents who drop out (DO) so the total the number of samples in this study were 66 people who were grouped into 2 groups (control group and treatment group) each group of 33 people. Data collection was carried out by visiting the Edelweiss Youth Integrated Healthcare Center and Berkabar Youth Integrated Healthcare for 3 visits starting in May 2021. The data generated is the behaviour (knowledge) of adolescents about anemia in the work area of the Tanjungpinang City Health Center in 2021 before and after being given the Monopoly Anemia Educational Game (GEMA) as one of the media innovation for Health Education. The results of data analysis using an independent simple t-test showed that there was an effect of using GEMA as a health education media on adolescent knowledge about anemia in the work area of the Tanjungpinang City Health Center in 2021.